The influence of the composition of liposomes on the encapsulation efficiency and the particle size when creating the liposomal form of cytochrome C - Katsai, Oleksii; Ruban, Olena; Krasnopolskyi, Yuriy (ScienceRise: Pharmaceutical Science, 2017)
The influence of the liposomes’ composition on the encapsulation degree and particle size in the pharmaceutical formulation of the liposomal form of Cytochrome C is studied. Aim: research of the effect of the composition of liposomes on the encapsulation efficiency and particle size when creating the liposomal form of Cytochrome C, as an agent for ophthalmic diseases therapy. Methods. Liposomal form of Cytochrome C is obtained by high pressure homogenization. Encapsulation of Cytochrome C was carried out using chemical bonding method, based on the possibility of formation of chemical bond between the liposome bilayer components and the active pharmaceutical ingredient. To determine the encapsulation efficiency, HPLC method based on the gel filtration was developed. The determination was carried out using Shimadzu (Japan) chromatograph. Results. The composition of liposome membrane that allows to obtain nanoparticles with high encapsulation degree of Cytochrome C – up to 95.88% and particle size in the range up to 150 nm – was determined. Conclusion: The optimal composition of the liposome membrane containing Dipalmitoylphosphatidylglycerol and Phosphatidylcholine was studied for the further study of the given liposomal complex as a therapeutic remedy in ophthalmology. It has been found that the optimal composition of liposomes is the ratio of Phosphatidylcholine and Dipalmitoylphosphatidylglycerol (1.2–4.0:1), ensuring the maximum encapsulation of Cytochrome C in liposomes. Methods for determination of encapsulation degree of Cytochrome C were developed. Cytochrome C encapsulation was more than 95.0 %